How do we manage asthma? Assessment of knowledge, attitude, and practice patterns among pulmonologists and allergists. (2nd January 2023) - Günaydın, Fatma Esra; Ay, Pınar; Karakaya, Gül; Ediger, Dane
Abstract: Objective: The objective of this study was to evaluate and compare knowledge, attitude, and practice patterns between pulmonologists and allergists for adult asthma in Turkey. Methods: Questionnaire-based data were gathered from 236 pulmonologists and 62 allergists, who had been members of the Turkish Thoracic Society and Turkish National Society of Allergy and Clinical Immunology in January–March 2021. Univariate and multivariate statistics were used to determine the factors associated with primary reliever preferences. Results : Of the 298 physicians, 39% encountered at least five asthma patients daily. Spirometer was used frequently by both the allergists (82.3%) and pulmonologists (77.5%) for asthma diagnosis. Budesonide was the most preferred inhaler corticosteroid. Formoterol/budesonide was the most preferred ICS/LABA combination, followed by beclomethasone/formoterol and fluticasone/salmeterol for asthma treatment. For mild asthmatics, formoterol/ICS was the most preferred (72.6%) reliever among allergists, whereas salbutamol was the most preferred (66.1%) among pulmonologists ( p  < 0.001). Age and workplace were associated with salbutamol preference of doctors for mild asthmatics. Age, specialty, and patient examination time were significantly associated with salbutamol preference for severe asthmatics. Conclusions : The use of diagnostic tools, such as a spirometer, for asthma diagnosis was compatible with the guidelines. While recent updates of the guidelines indicate that salbutamol should not be used solely in mild asthmatics due to its harmful effects in long-term use, it still was the most preferred drug by pulmonologists. Postgraduate education programs are needed to improve compliance with the guidelines.